INDUCTION OF RESISTANCE AGAINST Fusarium equiseti IN Spinacia oleraceae BY Catharanthus roseus AND EXPRESSION ANALYSIS OF STRESS-RELATED GENES - Shazia Shafique; Sobiya Shafique; Ayesha Mubarak; Rubab Rafique; Muhammad Faiq Irfan (Journal of Animal and Plant Sciences, 2026)
Spinacia oleraceae L. is a significant food vegetable, and it is vital to enhance its yield against the stress of many devastating pathogens such as Fusarium spp. The manipulation of plant extracts may mitigate the detrimental effects of disease-causing fungi. The antifungal activity of Catharanthus roseus methanolic extracts was investigated against the Fusarium equiseti pathogen, which causes leaf spot disease in spinach. Moreover, the elicited expression of the stress genes of C. roseuswas also explored. Antifungal bioassays revealed that increased concentration of leaf methanolic extracts significantly suppressed pathogen development. However, leaf extract exhibited maximum inhibition (approx. 95%) in fungal biomass production. The methanolic extract of C. roseus utilized in pot trials for biocontrol assays offered superior plant defense against pathogens, delivering the highest level of disease protection. Subsequently, RT-PCR was performed using ETR1, ETR2, and ESR1 coding genes to examine variations in the expression profiles of ethylene-related genes under pathogenic stress in C. roseus. The results concluded that either individual or synergistic higher expression of the ETR2 gene may suppress the growth of the pathogen, demonstrating its efficacy in controlling the disease.
Keywords: Catharanthusroseus; Biocontrol potential; Fusarium equiseti; Methanolic extract; stress genes; RT-PCR; Spinach